Poland’s Innovativeness Against The Background Of EU Countries (Recent Research Results) - Mikołajczyk, Bożena (Comparative Economic Research. Central and Eastern Europe, 2015)
Innovativeness in Europe has been a formulated goal of the EU since the Lisbon Strategy. One of the goals of the new Europe 2020 Strategy is smart growth, i.e. growth based on knowledge and innovation. This requires improving the quality of education and research results, the transfer of knowledge and innovations between countries, and broader commercialization of research results. Hence, the measurement of innovation evolves in order to reflect the factors that determine the level of innovativeness of economies. The purpose of this paper is to present the level of Poland’s innovativeness against the background of the EU countries, using the SII (Summary Innovation Index).